PENETAPAN KADAR RHODAMIN B DAN NATRIUM BENZOAT PADA SAUS TOMAT YANG BEREDAR DI WILAYAH PASAR INPRES KOTA PALU - Wardanita, Wardanita; Jura, Minarni Rama; Tangkas, I Made (Universitas Tadulako, 2013)
This research was conducted to determine the level of a dye, rhodamin B, and a preservative, benzoic acid, on tomato sauce distributed in the area of Palu city. The food additive is used in order to get more interesting color and the benzoic acid is used to keep the food fresh for a long period of time. The research method used was a thin layer chromatography. It was aimed at knowing weather there was a dye called rhodamin B in the research sample or not. From the analysis result, it can be said that the sample did not contain the dye rhodamin B. in addition, another research method used was alkali acid titration which was used to examine the sample quantitatively and qualitatively. From the qualitative examination, it was found that all tomato sauced sampled positively contained the preservative benzoic acid. The tomato sauce produced by Mojokerto-Indonesia contained 34.7mg/kg while the one produced by Urabaya-Indonesia contained 40mg/kg. In conclusion, (1) all sample of tomato sauce examined did not contain Rhodamin B,the red dye substance, which was forbidden to be used for food, cosmetics, and medicine according to the Health Ministerial Regulation of Indonesian Republic No. 722/Menkes/Per/IX/1988 concerning food composition; and (2) the content level of Benzoic Acid in tomato sauce spread out in the traditional market, Inpres, Palu city has fulfilled the standard, i.e. + 1000 mg/kg. However, it is expected that all people must still be careful when buying and using tomato sauce.